Inhibition of herpes simplex virus replication by methyl daunosamine. - Spivack, J G (1982)
Methyl daunosamine inhibited the replication of herpes simplex virus type 1 in a dose-dependent manner. The growth of the host Vero cells was not affected by daunosamine levels that had significant antiviral activity (2.5 mM) but was inhibited by concentrations of 5 mM or greater. Methyl daunosamine appears to be unique among the sugars with antiviral activity because at antiviral concentrations it did not inhibit the glycosylation of macromolecules.